1971
DOI: 10.1111/j.1365-2184.1971.tb01515.x
|View full text |Cite
|
Sign up to set email alerts
|

CYTOKINETIC ANALYSIS of SLOWLY PROLIFERATING BONE MARROW CELLS DURING RECOVERY FROM RADIATION INJURY

Abstract: A continuous administration of tritiated thymidine (3H‐TdR) into pregnant rats results in a complete labelling of the offspring. Further injections with 3H‐TdR for 26 days maintained the 100% labelling. Four weeks after discontinuation of 3H‐TdR application, distinct classes of cytokinetically resting labelled bone marrow cells were detected. These animals received X‐irradiation of the body with 750 R with one leg shielded, or X‐irradiation of one leg with 750 R, or X‐irradiation of one leg with 1500 R. In non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
1

Year Published

1971
1971
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
(7 reference statements)
3
8
1
Order By: Relevance
“…Therefore, the interpretation would again be that only few, if any, of these cells did react to antigen stimula tion. Similar findings could be demonstrated under regeneratory demand [6,7]. However, the reticular cells and histiocytes of the spleen showed a decrease of their labelling index without a marked diminuation of the mean grain count.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Therefore, the interpretation would again be that only few, if any, of these cells did react to antigen stimula tion. Similar findings could be demonstrated under regeneratory demand [6,7]. However, the reticular cells and histiocytes of the spleen showed a decrease of their labelling index without a marked diminuation of the mean grain count.…”
Section: Discussionsupporting
confidence: 74%
“…In the spleen of mice only 0.10-0.20 immuno competent cells for a specific antigen could be detected per 10° cells [1,2,8], Therefore, the conclusion would be that under immune stimulation, the mass of long-living lymphocytes does not react in the sense of a trans formation or proliferation. In contrast to that behaviour, as could be shown in previous work, the mass of bone-marrow lymphocytes did react under regeneratory stimulus [6,7].…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The term endothelial cells is meant for both the sinusoidal lining cells and the true vascular endothelial cells (for detailed description see else where [9,11]). It was shown that after administration of X-irradiation or cytotoxic agents [1,10,13] during the regeneratory process the frac tion of small mononuclear cells called 'resting bone marrow lymphocytes' could be stimulated to proliferate. However, there was no evidence for a stimulation of reticular or endothelial cells demonstrable in these investi gations.…”
mentioning
confidence: 99%
“…It has been shown that these cells have a short life in the bone marrow (Elves 1972). There are few long-lived lymphocytes in the rodent bone marrow (Haas et al 1971). Morphologically there are little differences among the bone marrow lymphocytes in rodents as well as in the human.…”
Section: Commentmentioning
confidence: 93%